1999
DOI: 10.1007/s004649901176
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopic performance in vivo with performance measured in a laparoscopic simulator

Abstract: Performance in an in vitro laparoscopic simulator correlated significantly with performance in an in vivo animal model. Practice in the simulator resulted in improved performance in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
122
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(125 citation statements)
references
References 8 publications
0
122
0
3
Order By: Relevance
“…19 Another report concluded that the performance in an in vitro laparoscopic simulator correlated signifi cantly with the performance in an in vivo animal model, 20 indicating that practice out of the operating room was able to improve performance in the operating room. Moreover, appropriate training requires an objective assessment system, so an objective assessment of endoscopic surgical skills is very important, not only for gaining the patient's trust, but for improving surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…19 Another report concluded that the performance in an in vitro laparoscopic simulator correlated signifi cantly with the performance in an in vivo animal model, 20 indicating that practice out of the operating room was able to improve performance in the operating room. Moreover, appropriate training requires an objective assessment system, so an objective assessment of endoscopic surgical skills is very important, not only for gaining the patient's trust, but for improving surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…47 Similarly, Fried and colleagues established the educational value of the McGill Inanimate System for Training and Evaluation of Laparoscopic Skills by showing evidence of its transfer validity to an animal model. 16,48,49 Transfer validity to the operating room has also been shown in two randomized controlled trials. 50,51 Finally, a 2006 systematic review of 14 studies involving a total of 261 participants found that video-based tower training is superior to either no training or conventional training.…”
Section: Synthetic Modelsmentioning
confidence: 84%
“…47 Similarly, Fried and colleagues established the educational value of the McGill Inanimate System for Training and Evaluation of Laparoscopic Skills by showing evidence of its transfer validity to an animal model. 16,48,49 Transfer validity to the operating room has also been shown in two randomized controlled trials. …”
mentioning
confidence: 84%
“…Live animals were used for practical exercises in the early years [142]. However due to ethical issues and costs, laparoscopic simulators were developed using inanimate box trainers and shown to be effective [143] [144]. Computer-based Virtual Reality (VR) platforms made a bigger impact on the medical community and currently are a state-of-the-art technique in medical training systems.…”
Section: Haptics In Simulation For Surgical Trainingmentioning
confidence: 99%